Factors associated with complete clearance of difficult common bile duct stones after temporary biliary stenting followed by a second ERCP: a multicenter, retrospective, cohort study - Jang, Dong Kee; Lee, Sang Hyub; Ahn, Dong Won; Paik, Woo Hyun; Lee, Jae Min; Lee, Jun Kyu; Ryu, Ji Kon; Kim, Yong-Tae (Endoscopy, 2020)
Background Although temporary endoscopic biliary stenting is considered effective for difficult common bile duct (CBD) stones, few studies have investigated the optimal conditions for complete stone clearance at the second endoscopic retrograde cholangiopancreatography (ERCP) after temporary biliary stenting. We aimed to evaluate factors associated with complete clearance.Methods Patients with difficult CBD stones (a large [≥ 20 mm] or multiple [≥ 3 sized ≥ 15 mm] CBD stones) were retrospectively enrolled from three institutions. Patients who underwent temporary biliary stenting at the first ERCP were analyzed. Double-pigtail plastic stents (7 or 10 Fr) were placed with the proximal ends above the stones. Complete clearance rate and stone size reduction at the second ERCP, and factors associated with complete clearance were evaluated using univariate and multivariate analyses.Results 85 patients were enrolled (mean age 74.5 years [SD 11.3]; 47 women). Stone size and CBD diameter significantly decreased during the interval. The overall complete stone clearance rate was 64.7 % (55/85) at the second ERCP. The mean stone size reduction was 5.6 mm (SD 6.8). In multivariate analysis, complete clearance rate was significantly lower in male patients, in patients aged > 80 years, and in stones > 25 mm initially, but was significantly higher when 7-Fr stents were placed and stone size was reduced by > 5 mm.Conclusion Use of 7-Fr rather than 10-Fr plastic stents was beneficial for complete clearance of difficult CBD stones after temporary biliary stenting; older male patients as well as patients with initial stones > 25 mm had a lower clearance rate.